Profesionalisme Guru Dalam Rangka Peningkatan Mutu Pendidikan - Sari, Desi Ratna; Sari, Novita; Hilmin Hilmin, Hilmin Hilmin (STAI Denpasar Bali, 2023)
The quality of education and teacher professionalism are interrelated so that the two cannot be separated, especially in the process of achieving educational goals. One thing that influences the quality of education is teacher professionalism because teachers are the determinants of the success and failure of a learning process so that this will influence the future of students. Currently, the quality of education in Indonesia is still far behind other countries. The current situation is that the level of teacher professionalism is still far from expectations, while students' academic achievements and results are influenced by teachers. Therefore, it is necessary to make a breakthrough so that the level of professionalism of teachers in Indonesia can be better and so that education in Indonesia can further develop and be able to compete with other countries.